Evaluating the Efficacy of Gum Arabic-Zinc Oxide Nanoparticles Composite Coating on Shelf-Life Extension of Mandarins (cv. Kinnow) - Nxumalo, Kwanele Andy; Fawole, Olaniyi Amos; Oluwafemi, Oluwatobi Samuel (Frontiers in Plant Science, 2022)
Restricted postharvest application of synthetic fungicides in maintaining the quality of citrus fruits has led researchers to find alternative methods such as applying edible coatings enriched with nanoparticles. This study evaluated the efficacy of gum arabic (GA) enriched with green synthesized zinc oxide nanoparticles (ZnO-NPs) in maintaining the postharvest quality of mandarin (cv. Kinnow). ZnO-NPs were synthesized using Bidens pilosa, leaf extract and incorporated into GA (2%) at 0%, 0.25%, 0.5% and 1% to form composite coatings, GA, GA+ZnO-NP 0.25%, GA+ZnO-NP 0.5% and GA+ZnO-NP 1%, respectively. Fruit were dipped for 3 min in respective coatings, with untreated fruit used as the control. Fruit were air-dried, packed in commercial cartons, and stored at 5±1 °C and 90±5% relative humidity (RH) for 40 d. Sampling was done at 10 d intervals. To determine the incidence of physiological disorders, the fruit were further stored at 20±5 °C and 65±5% RH for 5 d. Results indicated that GA+ZnO-NP composite coating maintained higher physicochemical attributes, phytochemical and antioxidant content, and controlled incidence of rind disorders compared to the control and GA. Weight loss (9.2%), electrolyte leakage (43.8%), and chilling injury incidence (5.4%) were effectively controlled by coating the fruit with GA+ZnO-NP 0.5% compared to control with values of 33.3%, 90.3%, and 41.5%, respectively. Coating the fruit with GA+ZnO-NP 1% resulted in a lower respiration rate (35.1 mL CO2/kg‧h), rind pitting incidence (13.2%), and higher ascorbic acid (63.56 mg AAE/100 mL KMFJ (‘Kinnow’ mandarin fruit juice) compared to control with values of 91.5 mL CO2/kg‧h, 45.2% and 39.73 mg AAE/100 mL KMFJ, respectively. This was due to significantly higher phytochemical and antioxidant capacity and reduced antioxidant enzyme degradation of coated fruit than control. Therefore, based on the correlation matrix and principal component analysis, we recommended GA+ ZnO-NP in the range of 0.5% and 1% treatments for further optimization for commercial adoption as safe preservation technology to maintain the quality of ‘Kinnow’ mandarin fruit during storage.